2019
DOI: 10.1002/ange.201901198
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective, High‐Capacity Separation of o‐Xylene from C8 Aromatics by a Switching Adsorbent Layered Material

Abstract: Purification of the C 8 aromatics (xylenes and ethylbenzene) is particularly challenging because of their similar physical properties.I ti sa lso relevant because of their industrial utility.Physisorptive separation of C 8 aromatics has long been suggested as an energy efficient solution but no physisorbent has yet combined high selectivity (> 5) with high adsorption capacity (> 50 wt %). Now ac ounterintuitive approach to the adsorptive separation of o-xylene from other C 8 aromatics involves the study of akn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Owing to their inherent diversity, these materials enable precise control of pore shape, pore chemistry and pore size, thereby providing a versatile platform for separation processes [8][9][10][11][12][13][14][15] . In terms of trace gas removal, numerous studies have focused on the rational design of three-dimensional (3D) MOFs with uniform sub-nanometer pores [16][17][18][19][20][21][22][23][24][25] . Despite significant achievements, designing new materials that outperform existing benchmark adsorbents remains a formidable challenge.…”
mentioning
confidence: 99%
“…Owing to their inherent diversity, these materials enable precise control of pore shape, pore chemistry and pore size, thereby providing a versatile platform for separation processes [8][9][10][11][12][13][14][15] . In terms of trace gas removal, numerous studies have focused on the rational design of three-dimensional (3D) MOFs with uniform sub-nanometer pores [16][17][18][19][20][21][22][23][24][25] . Despite significant achievements, designing new materials that outperform existing benchmark adsorbents remains a formidable challenge.…”
mentioning
confidence: 99%
“…Porous materials with designable pore topology and selective binding sites open up unexpected possibilities for recognition of xylene isomers [13][14][15][16][17][18][19][20] . Different kinds of metal-organic frameworks (MOFs) or porous coordination polymers, including MIL (Materials of Institut Lavoisier) series and MOFs with coordinatively unsaturated metal sites (CUSs), have been investigated for the separation of xylene isomers, both in vapor and liquid phases [21][22][23][24][25][26][27][28][29][30][31] . However, MIL-47 and MIL-125-NH 2 can hardly discriminate pX and mX, and the pX/mX selectivity of MIL-47 is 1.1 (calculated from breakthrough data) 23 .…”
mentioning
confidence: 99%
“…To better understand stepwise the C 2 H 2 isotherms exhibited by sql-1-Cu-BF 4 , molecular simulations using the density functional theory (DFT) were conducted based on structural analogues. 44 , 47 , 57 As revealed by Figure 5 , C 2 H 2 molecules (violet) occupy the interlayer space in sql-1-Cu-BF 4 ·1C 2 H 2 ( Figure 5 a) and sql-1-Cu-BF 4 ·2C 2 H 2 ( Figure 5 b). Extra C 2 H 2 molecules (red) reside in the square cavity for sql-1-Cu-BF 4 ·6C 2 H 2 ( Figure 5 c) and sql-1-Cu-BF 4 ·8C 2 H 2 ( Figure 5 d).…”
Section: Resultsmentioning
confidence: 88%
“…We have studied the sorption behavior of the square lattice ( sql ) coordination network [Co(bpy) 2 (NCS) 2 ] n (bpy = 4,4′-bipyridine), sql-1-Co-NCS , and found that it exhibits a reversible switching behavior induced by CO 2 or C 8 aromatic isomers. 46 , 47 Although sql-1-Co-NCS is a type of FMOM, its sudden switching behavior makes it distinctive 48 and more desirable than FMOMs with type F-I or F-II isotherms. 49 , 50 We classified this type of 2D MOM as a switching adsorbent layered material (SALMA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation